2010
DOI: 10.1172/jci41414
|View full text |Cite
|
Sign up to set email alerts
|

p120-catenin is essential for maintenance of barrier function and intestinal homeostasis in mice

Abstract: Epithelial-cadherin (E-cadherin) is a master organizer of the epithelial phenotype. Its function is regulated in part by p120-catenin (referred to herein as p120), a cytoplasmic binding partner that directly regulates cadherin stability. As it has been suggested that cadherins have a role in inflammatory bowel disease (IBD), we sought to investigate this further by assessing the effect of p120 deficiency in mouse small intestine and colon. p120 conditional KO mice were superficially normal at birth but decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(170 citation statements)
references
References 68 publications
13
155
2
Order By: Relevance
“…Another mechanism that could relate to the severe epithelial phenotype is the loss of the cadherin/catenin complex and links to the cytoskeleton. For example, p120-catenin KO mice are characterized by disturbed epithelial adhesion, increased inflammation, mucosal erosions, and bloody stools, effects similar to what has been observed in the study by Grill and colleagues [12]. Thus, it will be important to investigate in future studies how colitis and loss of E-cadherin affect catenin functions and the cytoskeleton, which are major factors for controlling epithelial barrier integrity.…”
supporting
confidence: 52%
“…Another mechanism that could relate to the severe epithelial phenotype is the loss of the cadherin/catenin complex and links to the cytoskeleton. For example, p120-catenin KO mice are characterized by disturbed epithelial adhesion, increased inflammation, mucosal erosions, and bloody stools, effects similar to what has been observed in the study by Grill and colleagues [12]. Thus, it will be important to investigate in future studies how colitis and loss of E-cadherin affect catenin functions and the cytoskeleton, which are major factors for controlling epithelial barrier integrity.…”
supporting
confidence: 52%
“…In contrast to our results, however, Smalley-Freed et al (2010) reported that knockout or knockdown of p120-catenin resulted in the down regulation of E-cadherin and breakage of adherens junction as predicted; but unexpectedly ZO-1 and occludin were still localized at cell-cell contact sites. We do not have a good explanation as to why the tight junction proteins were localized without adherens junction in the experiments, in contrast to the general notion that E-cadherin is required for the localization (Itoh et al, 1993).…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Smalley-Freed et al (2010) reported knockdown experiments on p120-catenin in cell culture, but the experiments also had the same problem. Meng et al (2008), on the other hand, suggested that p120-catenin-binding proteins participate in cell polarity formation.…”
Section: Introductionmentioning
confidence: 99%
“…117 However, mice with intestinal epithelial loss of P120-catenin have increased intestinal permeability associated with a severe inflammatory phenotype and abnormal intestinal architecture. 118 JAM-A is down-regulated during inflammatory bowel disease and, as highlighted above, its loss is associated with potent effects on epithelial barrier and homeostasis. However, in contrast to the phenotypes observed with claudin-1 and P120-catenin knockout mice, JAM-Aedeficient mice do not get spontaneous colitis despite significantly increased intestinal permeability.…”
Section: Modeling Loss Of Tight Junction Proteins In Animals Has Provmentioning
confidence: 96%